Efficiency evaluation of manufacturing thin porous shells by extrusion - Томаш, Гарбач; Красінський, Володимир Васильович; Суберляк, Олег Володимирович; Дулебова, Людмила (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents the results of investigating the porous extrusion process of the polyvinyl chloride (PVC) cable shell in the presence of different-nature blowing agents. The aim was to develop a technological process of manufacturing the porous insulating polyvinyl chloride shell of the power cable by extrusion and explore the structure and performance properties of the resulting shell. Based on experimental data, optimal process parameters of manufacturing the porous insulating polyvinyl chloride shell of the power cable by the extrusion were found. The structure and performance properties of the porous shell were examined. It is shown that using endothermic blowing agents in the amount of 0,2-0,8% and exothermic blowing agents in the amount 0.4-0.6% in the extrusion of power cable PVC-shell allows to obtain high-quality product, the cost of which is significantly lower than of the monolithic PVC shell. It is shown that the obtained insulating shell meets national and international requirements.